DEBT DEFAULT, IFRS IMPLEMENTATION, AND FOREIGN OWNERSHIP TO GOING CONCERN AUDIT OPINION - Kenny Ardillah; Samuel Oscar Prawira (Riset Akuntansi Keuangan, 2022)
The purpose of the study is to test the effect of debt default, IFRS implementation, and foreign ownership on going concern audit opinion. This study used the purposive sampling method. This research sample was taken from all listed manufacturing companies registered in Indonesia Stock Exchange from 2017-2019. The data analysis method used in this study is descriptive analysis with the analytical method used in testing the hypothesis in this study using the logistic regression method. The results achieved from this study were that debt default has a positive influence on the going concern audit opinion, while IFRS implementation and foreign ownership have a negative influence on the going concern audit opinion.